1997
DOI: 10.1002/lipi.19970991206
|View full text |Cite
|
Sign up to set email alerts
|

Selective improvement of porcine fat firmness by a diet enriched in medium‐chain fatty acids

Abstract: The effects Of 4% fat either rich in medium-chain fatty acids (MCFA; saturated fat) or in polyenoic fatty acids (PUFA; unsaturated fat) isoenergetically exchanging carbohydrates of a low-fat diet (control) on performance and product quality were evaluated with 180 growing pigs. Growth, carcass and meat quality were not affected by the fat treatments. Although elevated in blood serum, cholesterol was not increased in belly meat when the MCFA-rich diet was fed. Fatty acid composition of backfat reflected dietary… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
10
1

Year Published

2001
2001
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 12 publications
4
10
1
Order By: Relevance
“…A correlation also emerged between the dietary content of myristic acid and the concentrations of myristic acid in adipose tissue. This suggests, in agreement with other studies [16,17], that an appreciable amount of dietary myristic acid is incorporated into adipose tissue. In quantitative studies with rats 29% of the myristic acid ingested with the diet was recovered in the residual body, substantially more than the recovery of lauric acid (10%), but less than that of palmitic acid (35%) [18].…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…A correlation also emerged between the dietary content of myristic acid and the concentrations of myristic acid in adipose tissue. This suggests, in agreement with other studies [16,17], that an appreciable amount of dietary myristic acid is incorporated into adipose tissue. In quantitative studies with rats 29% of the myristic acid ingested with the diet was recovered in the residual body, substantially more than the recovery of lauric acid (10%), but less than that of palmitic acid (35%) [18].…”
Section: Discussionsupporting
confidence: 81%
“…This finding is not surprising given that all three fats used are highly digestible. Other studies have also shown that the type of dietary fat does not affect performance parameters and carcass composition of finishing pigs, provided that either highly digestible fats are used or that the metabolizable energy of the fats is taken into account [1,13,14,15,16].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One reason for the high transfer of added fatty acids could be the reduced de novo synthesis of fatty acids in the body if higher fat amounts are fed (Kijora et al, 1997;Kreuzer et al, 1997). Oleic acid in the depot fat came from oleic acid in feed and from stearic acid through the activity of stearoyl-CoA-desaturase in liver and fat tissue (Klingenberg et al, 1995).…”
Section: Resultsmentioning
confidence: 99%
“…The objective of the present investigation was to follow the effects of different types and amounts of fermentable dietary fibre in growing pigs on cholesterol and cholesterol‐related lipids in blood serum, bile and body tissues. Furthermore, interactions with the type of dietary fat were measured since fats are also known to substantially influence body cholesterol metabolism (B OHAC and R HEE 1988; K REUZER et al. 1997; W ILLIAMS 2000) and therefore might support or prevent effects of fibre.…”
Section: Introductionmentioning
confidence: 99%